2023
DOI: 10.1021/jacs.3c01108
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Interferometric Effects between Single-Molecule Suzuki–Miyaura Cross-Couplings

Abstract: Parallel two molecular bridges loaded with a palladium catalyst were integrated into separate pairs of graphene electrodes in the same device. Based on the complete description of the one-palladium catalytic pathway by single-molecule electrical spectroscopy, this setup enables the mapping of the crosscorrelation between different catalysts and demonstrates the emergent complexity in the extrapolation from single molecule to ensemble. The anticorrelation behaviors at the time scale of two individual catalysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…A number of breakthrough works have been carried out to highlight the processes in dynamic catalysis. The dynamic behavior of gold particles in catalytic reactions has been studied by Hutchings and co-workers. The behavior of platinum, palladium, iridium particles was studied by Corma and co-workers. Growth, leaching and redeposition of/from palladium nanoparticles in cross-coupling reactions was investigated by Köhler and co-workers. ,, The dynamic behavior of palladium and the formation of [PhPdI 2 ] − and [PdI 3 ] − complexes, as well as palladium nanoparticles from soluble complexes, were studied by Reetz, de Vries and co-workers. Pérez-Ramírez and co-workers were actively investigating catalytic processes using computational methods and ML. Gai, Boyes and co-workers have contributed to the study of specific sites of the catalyst by ETEM methods. A study of the behavior of a specific Pd/NHC (NHC – N-heterocyclic carbene) catalyst molecule in cross-coupling reactions was conducted by Guo and co-workers. In a series of studies, Weckhuysen and co-workers have shown the relationship between the structure and activity of heterogeneous catalysts in industrially significant catalytic transformations, including for individual catalyst particles. The fundamental results of these and other research groups have firmly established the fact that the catalytically active particles in the reaction system should be investigated at a new combined experimental and ML level. Currently, it is clearly evident that, for a deeper study of catalytic processes, it is necessary to trace the life path of individual catalytic centers and particles.…”
Section: Analysis Of the Dynamic Behavior And Variability Of Catalyti...mentioning
confidence: 99%
See 2 more Smart Citations
“…A number of breakthrough works have been carried out to highlight the processes in dynamic catalysis. The dynamic behavior of gold particles in catalytic reactions has been studied by Hutchings and co-workers. The behavior of platinum, palladium, iridium particles was studied by Corma and co-workers. Growth, leaching and redeposition of/from palladium nanoparticles in cross-coupling reactions was investigated by Köhler and co-workers. ,, The dynamic behavior of palladium and the formation of [PhPdI 2 ] − and [PdI 3 ] − complexes, as well as palladium nanoparticles from soluble complexes, were studied by Reetz, de Vries and co-workers. Pérez-Ramírez and co-workers were actively investigating catalytic processes using computational methods and ML. Gai, Boyes and co-workers have contributed to the study of specific sites of the catalyst by ETEM methods. A study of the behavior of a specific Pd/NHC (NHC – N-heterocyclic carbene) catalyst molecule in cross-coupling reactions was conducted by Guo and co-workers. In a series of studies, Weckhuysen and co-workers have shown the relationship between the structure and activity of heterogeneous catalysts in industrially significant catalytic transformations, including for individual catalyst particles. The fundamental results of these and other research groups have firmly established the fact that the catalytically active particles in the reaction system should be investigated at a new combined experimental and ML level. Currently, it is clearly evident that, for a deeper study of catalytic processes, it is necessary to trace the life path of individual catalytic centers and particles.…”
Section: Analysis Of the Dynamic Behavior And Variability Of Catalyti...mentioning
confidence: 99%
“…Thus, in the work of Guo and co-workers, Suzuki–Miyaura and Mizoroki–Heck reactions were carried out on a single Pd/NHC catalyst molecule, and the authors detailed the study mechanism and found new intermediates for this system. The use of two fixed Pd/NHC molecules in the catalysis of Suzuki–Miyaura reactions showed that the solvent-induced long-range electric dipole–dipole interaction leads to a destructive interferometric effect of two closely spaced catalyst molecules . LP EM has also been used to study multicomponent catalytic systems for liquid-phase C–S cross-coupling reactions .…”
Section: Analysis Of the Dynamic Behavior And Variability Of Catalyti...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Denmark et al made a significant breakthrough in unveiling pre-transmetalation intermediates at basic conditions and suggested palladium hydroxo complexes could react with aryl boronic acids to afford palladium boronate through the low-temperature rapid injection nuclear magnetic resonance spectroscopy and kinetic studies . Since then, Denmark, Suranna, Bissember, Vetticatt, Chirik, , Guo, , and Schmidt have performed numerous studies on the metal boronate pre-transmetalation intermediates. It should be noted that the conversions of metal halide complexes into the metal hydroxo or metal boronate pre-transmetalation intermediates require basic conditions (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…37 studies. 38 Since then, Denmark, 39−41 Suranna, 42 Bissember, 43−45 Vetticatt, 46 Chirik, 47,48 Guo, 49,50 and Schmidt 51 have performed numerous studies on the metal boronate pre-transmetalation intermediates. It should be noted that the conversions of metal halide complexes into the metal hydroxo or metal boronate pre-transmetalation intermediates require basic conditions (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%